ANALISIS PERILAKU WAJIB PAJAK TERKAIT DENGAN RANGKAIAN PENYAMPAIAN SURAT TUNGGAKAN PAJAK KENDARAAN BERMOTOR (Studi Kasus UPT Dispenda Jawa Timur Malang Utara dan Batu Kota) - Nindia Agrina Yularsa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is aim to know the simultanously and partially influences of letters arrears motor vehicle tax to the tax payer’s behaviour which is analyzed by motor vehicle tax revenues variable. Afterwards, the researcher also analyze about the dominantly pattern of letters arrears motor vehicle tax influential effort to increase motor vehicle tax revenues. This research is conducted in East Java Dispenda in Technical Unit Office of North Malang and Batu City.The research sample is 51 secondary data from 2009 to 2013 fiscal year to be researched. The research method is the Multiple Linier Regression Method using Ordinary Least Square (OLS). The result shows that: the assessmentof regions tax, the receivable of regions tax, and the institutional of regions tax are together influenced the tax payer’s behaviour topromptly settletheir taxarrears. According to the partial test, the researcher conclude that the assessmentof regions tax and the institutional of regions tax has significant positive influenced the tax payer’s behaviour topromptly settletheir taxarrears, whereas the receivable of regions tax has insignificantnegativeinfluence. The multiple regressionanalyzes that been used to figure out about the dominantly pattern of letters arrears motor vehicle tax influential to motor vehicle tax revenues provide that the assessmentof regions tax has a major contribution for any increase of motor vehicle tax revenues. Keywords : tax payer’s behaviour, letter oftaxarrears, effort to increase motor vehicletaxrevenue, motor vehicle tax